Integrative omics data analyses of repeated dose toxicity of valproic acid in vitro reveal new mechanisms of steatosis induction. (15th January 2018) - van Breda, Simone G.J.; Claessen, Sandra M.H.; van Herwijnen, Marcel; Theunissen, Daniël H.J.; Jennen, Danyel G.J.; de Kok, Theo M.C.M.; Kleinjans, Jos C.S.
Abstract: Valproic acid (VPA) is a very potent anti-cancer and neuro-protective drug probably by its HDAC inhibiting properties, which may cause steatosis in the liver. The present study investigates the effect of repetitive VPA treatment of primary human hepatocytes (PHH) on whole genome gene expression-, DNA methylation-, and miRNA changes, using microarrays and integrated data analyses. PHH were exposed to a non-cytotoxic dose of VPA for 5 days daily which induced lipid accumulation. Part of the PHH was left untreated for 3 days for studying the persistence of 'omics' changes. VPA treatment appeared to inhibit the expression of the transcription factors HNF1A and ONECUT1 . HNF1A interacted with 41 differentially expressed genes of which 12 were also differentially methylated. None of the genes present in this network were regulated by a DE-miR. The subnetwork of ONECUT1 consisted of 44 differentially expressed genes of which 15 were differentially methylated, and 3 were regulated by a DE-miR. A number of genes in the networks are involved in fatty acid metabolism, and may contribute to the development of steatosis by increasing oxidative stress thereby causing mitochondrial dysfunction, and by shifting metabolism of VPA towards β-oxidation due to reduced glucuronidation. Part of the changes remained persistent after washing out of VPA, like PMAIP1 which is associated with cellular stress in liver of patients with NASH. The MMP2 gene showed the highest number of interactions with other persistently expressed genes, among which LCN2 which is a key modulator of lipid homeostasis. Furthermore, VPA modulated the expression and DNA methylation level of nuclear receptors and their target genes involved in the adverse outcome pathway of steatosis, thereby expanding our current knowledge of the pathway. In particular, VPA modulated PPARγ, and PPARα, AHR and CD36 on both the gene expression and the DNA methylation level, thereby inhibiting β-oxidation and increasing uptake of fatty acid into the hepatocytes, respectively. Overall, our integrative data analyses identified novel genes modulated by VPA, which provide more insight into the mechanisms of repeated dose toxicity of VPA, leading to steatosis.